2013
DOI: 10.1016/j.apmr.2013.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Capacity to Participation in Cerebral Palsy: Evidence of an Indirect Path Via Performance

Abstract: Objective To examine the hypothesis that the influence of physical activity capacity on participation is mediated through activity performance. Design Secondary analysis of a prospective cross-sectional study sample. Setting Regional pediatric specialty care hospital. Participants Children (N = 128; 59% boys; age range, 2–9y) with cerebral palsy with Gross Motor Function Classification System levels I to III; 49% had hemiplegia, and 72% had spasticity. Interventions Not applicable. Main Outcome Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…New literature has documented that the relationship of what a child is “able” to perform in a clinic setting and their participation in life is significantly mediated by what they physically “actually” do each day in ambulatory children with CP [21]. These results suggest that participation in day-to-day life maybe positively influenced by interventions focusing on improving what they actually do every day regardless of capacity to perform.…”
Section: Introductionmentioning
confidence: 97%
“…New literature has documented that the relationship of what a child is “able” to perform in a clinic setting and their participation in life is significantly mediated by what they physically “actually” do each day in ambulatory children with CP [21]. These results suggest that participation in day-to-day life maybe positively influenced by interventions focusing on improving what they actually do every day regardless of capacity to perform.…”
Section: Introductionmentioning
confidence: 97%
“…Capacity refers to an individual's ability to execute a task or action in a standardized environment [2]. Performance describes the individual's execution of a task or action in the natural environment [2]. Knowledge of the factors that influence physical activity capacity and performance may allow therapists to develop more effective physiotherapy interventions for children with an ABI.…”
Section: Introductionmentioning
confidence: 99%
“…Activity outcomes can be divided into capacity and performance qualifiers. Capacity refers to an individual's ability to execute a task or action in a standardized environment [2]. Performance describes the individual's execution of a task or action in the natural environment [2].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this systematic review confirmed that HPA was directly associated with motor capacity in children with CP aged 2-17 years. A metaanalysis could not be performed in this study because the HPA measurements across studies included both subjective 15,[68][69][70] and objective measures. 14,[30][31][32][33][34] The objective HPA measurements were the StepWatch® 14, 30-33 and the ActiGraph®.…”
Section: Overviewmentioning
confidence: 99%
“…15,69,70 Additionally, three studies recruited children with CP from 2 years of age, but only ambulant children (GMFCS I-III) were observed. 32,33,68 No study investigated HPA using objective measurements in all functional abilities of children with CP. In addition, data on HPA in non-ambulant children with CP is not available.…”
Section: Overviewmentioning
confidence: 99%